5 Hz repetitive transcranial magnetic stimulation to left prefrontal cortex for major depression - Philip, Noah S. (J Affect Disord, 2015)
BACKGROUND: Repetitive transcranial magnetic stimulation (rTMS) to left prefrontal cortex at 10 Hz is the most commonly utilized protocol for major depressive disorder (MDD). Published data suggests that left sided 5 Hz rTMS may be efficacious and well tolerated. OBJECTIVE: We analyzed outcomes in a naturalistic cohort of MDD patients who could not tolerate 10 Hz rTMS and were routinely switched to 5 Hz. We hypothesized that the efficacy of 5 Hz rTMS would be equivalent to 10 Hz. METHODS: Records were reviewed for patients (n=98) who received 15 or more acute rTMS treatments. The sample was split based upon the frequency (10 or 5 Hz) at which the majority of treatments were delivered. The Inventory of Depressive Symptoms (IDS-SR) and 9-Item Patient Health Questionnaire (PHQ-9) were used to evaluate outcomes. RESULTS: Baseline IDS-SR was higher in the 5 Hz (n=27) than in the 10 Hz (n=71) group (p < .05), as was frequency of comorbid anxiety (p = .002). Depression outcomes did not differ between groups, and there were no differences in response or remission rates (all p > .1). Statistical power was sufficient to detect small group differences (d = .26). LIMITATIONS: Open-label data in a naturalistic setting. CONCLUSION: Outcomes associated with 5 Hz rTMS did not differ from 10 Hz, despite higher baseline depressive symptom severity and anxiety in 5 Hz patients. 5 Hz stimulation may be an alternative treatment option for patients unable to tolerate 10 Hz rTMS.